2019
DOI: 10.18632/oncotarget.27225
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized in vivo pH imaging reveals grade-dependent acidification in prostate cancer

Abstract: There is an unmet clinical need for new and robust imaging biomarkers to distinguish indolent from aggressive prostate cancer. Hallmarks of aggressive tumors such as a decrease in extracellular pH (pHe) can potentially be used to identify aggressive phenotypes. In this study, we employ an optimized, high signal-to-noise ratio hyperpolarized (HP) 13C pHe imaging method to discriminate between indolent and aggressive disease in a murine model of prostate cancer. Transgenic adenocarcinoma of the mouse prostate (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
3
18
0
1
Order By: Relevance
“…We hypothesized that pH e would decrease based on prior data indicating increased production of lactic acid in high-grade tumors [62], as well as the observation that treatment with sodium bicarbonate blocked tumorigenesis in this model [63]. Supporting the hypothesis, we found that there was a significant decrease in pH e in mice bearing high-grade tumors compared against low-grade counterparts [64]. Therefore, there is an accumulating body of both indirect and direct evidence supporting the hypothesis that a temporal decrease in pH e could represent a biomarker of tumor disease progression.…”
Section: Ph Heterogeneity In Timesupporting
confidence: 57%
“…We hypothesized that pH e would decrease based on prior data indicating increased production of lactic acid in high-grade tumors [62], as well as the observation that treatment with sodium bicarbonate blocked tumorigenesis in this model [63]. Supporting the hypothesis, we found that there was a significant decrease in pH e in mice bearing high-grade tumors compared against low-grade counterparts [64]. Therefore, there is an accumulating body of both indirect and direct evidence supporting the hypothesis that a temporal decrease in pH e could represent a biomarker of tumor disease progression.…”
Section: Ph Heterogeneity In Timesupporting
confidence: 57%
“…As in other cancers, acidic microenvironments in prostate cancer are also considered to be an important prognostic factor (23). Acidic pH o can be used as a robust imaging biomarker for aggressive prostate cancer (24). Pharmacological inhibition or knockdown of several acid extrusion transporters, such as Na/H exchangers NHEs (25), V-ATPases (26,27) and monocarboxylate transporters MCTs (28), prevents prostate cancer progression in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…But the technique may have even more to offer in prognostication, patient selection and early treatment evaluation. For example, from the field of oncology, metabolic assessment with hyperpolarized MRI is reported to correlate with tumor grade ( 36 , 51 , 52 ) and depict the early metabolic response to chemotherapy ( 32 , 53 , 54 ). In cardiology, hyperpolarized MRI could be useful for selecting patients for novel metabolic or pH-altering therapy in heart failure ( 1 ), or for detecting the severity, reversibility and localization of ischemia in coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%